Eldest - Paolini, Christopher; Palencar, John Jude (New York : Alfred A. Knopf Distributed by Random House, 2005)
After successfully evading an Urgals ambush, Eragon is adopted into the Ingeitum clan and sent to finish his training so he can further help the Varden in their struggle against the Empire.
A twin disaster -- The Council of Elders -- Truth among friends -- Roran -- The hunted hunters -- Saphira's promise -- Requiem -- Fealty -- A sorceress, a snake, and a scroll -- Hrothgar's gift -- Hammer and tongs -- Retaliation -- Az Sweldn rak Anhuin -- Celbedeil -- Diamonds in the night -- Under a darkling sky -- Dow the rushing mere-wash -- Drifting -- Arya Svit-kona -- Ceris -- Wounds of the past -- Wounds of the present -- His enemy's face -- Arrow to the heart -- The Dagshelgr Invocation -- The pinewood city -- Queen Islanzadi -- Out of the past -- Conviction -- Repercussions -- Exodus -- On the crags of Tel'naeir -- The secret lives of ants -- Under the menoa tree -- A maze of opposition -- Hanging by a thread -- Elva -- Resurgence -- Why do you fight? -- Black morning glory -- The nature of evil -- Image of perfection -- The obliterator -- Narda -- The hammer falls -- The beginning of wisdom -- Broken egg and scattered nest -- The gift of dragons -- In a starry glade -- Landfall -- Teirm -- Jeod Longshanks -- An unexpected ally -- Escape -- Child's play -- Premonition of war -- Red blade, white blade -- Visions near and far -- Gifts -- The maw of the ocean -- Running the boar's eye -- To Aberon -- The burning plains -- The clouds of war -- Nar Garzhvog -- Witch's brew -- The storm breaks -- Convergence -- Eldest -- Inheritance -- Reunion -- Pronunciation guide and glossary -- Extra scene from Eldest -- A special preview of Brisingr.
Map on endpapers.
Jacket illustration copyright 2005 by John Jude Palencar.
For young adults.
Accelerated Reader
Reading Counts
Accelerated Reader AR
Keywords: Dragons -- Fiction; Fantasy fiction; Fantasy; Dragons -- Fiction; Youths' writings; Dragons; Fantasy fiction; Dragons -- Fiction; Fantasy fiction; Fantasy fiction; Fantasy; Fantasy; Fantasy fiction -- Young adult; Fantasy fiction; Fiction; Fantasy fiction